"Host in Host" Supramolecular Core–Shell Type Systems Based on Giant Ring‐Shaped Polyoxometalates. (31st March 2021) - Falaise, Clément; Khlifi, Soumaya; Bauduin, Pierre; Schmid, Philipp; Shepard, William; Ivanov, Anton A.; Sokolov, Maxim N.; Shestopalov, Michael A.; Abramov, Pavel A.; Cordier, Stéphane; Marrot, Jérôme; Haouas, Mohamed; et al.
Abstract: Herein, we show how the chaotropic effect arising from reduced molybdate ions in acidified aqueous solution is able to amplify drastically weak supramolecular interactions. Time‐resolved Small Angle X‐ray Scattering (SAXS) analysis suggests that molybdenum‐blue oligomeric species form huge aggregates in the presence of γ‐cyclodextrin (γ‐CD) which results in the fast formation of nanoscopic Mo154 ‐based host‐guest species, while X‐ray diffraction analysis reveals that the ending‐point of the scenario results in an unprecedented three‐component well‐ordered core–shell‐like motif. A similar arrangement was found by using preformed hexarhenium chalcogenide‐type cluster [Re6 Te8 (CN)6 ] 4− as exogenous guest. This seminal work brings better understanding of the self‐assembly processes in general and gives new opportunities for practical applications in the design of complex multicomponent materials via the simplicity of the non‐covalent chemistry. Abstract : γ‐cyclodextrin has dramatic consequences on the solution behaviour of molybdates. Small angle X‐ray scattering analysis (SAXS) reveals the formation of large nanoscopic Mo‐based oligomers that give rise to the fast formation of supramolecular core–shell type systems. This behaviour has been attributed to the chaotropic effect able to amplify very weak supramolecular interaction and then generates sophisticated non‐covalent hierarchical assemblies.